2009
DOI: 10.1364/oe.17.016342
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrary waveform synthesis by multiple harmonics generation and phasing in aperiodic optical superlattices

Abstract: The process of generating periodic optical waveforms includes the generation and phasing of several harmonics of a fundamental frequency. In this work, we show that simultaneous generation and phasing of the harmonics can be performed in a monolithic aperiodic optical superlattice (AOS). Stable periodic waveforms can thus be delivered to a predetermined location by simply sending a laser beam through a properly designed and fabricated AOS crystal. A detailed mathematical description for generating the domain p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The coupling between the target eigenstate and the other eigenstates is much smaller than the difference among them to keep the process in the state of adiabatic evolution. The adiabatic condition can be described as follows [19]: Phase reversal quasi-phase-matching (PRQPM) is used to modulate the second-order nonlinear coefficient (2)  in the optic crystals [20][21][22]. Pragati et al designed a series of structures in the optical crystal by mainly using two different quasi-phase-matching (QPM) grating structures in a hybrid planar-channel waveguide to achieve the two cascaded wavelength conversion process with STIRAP mechanism effects, and they realized the of two coupling coefficients in the construction of an adiabatic process in the action length [23].…”
Section: Stproducesmentioning
confidence: 99%
“…The coupling between the target eigenstate and the other eigenstates is much smaller than the difference among them to keep the process in the state of adiabatic evolution. The adiabatic condition can be described as follows [19]: Phase reversal quasi-phase-matching (PRQPM) is used to modulate the second-order nonlinear coefficient (2)  in the optic crystals [20][21][22]. Pragati et al designed a series of structures in the optical crystal by mainly using two different quasi-phase-matching (QPM) grating structures in a hybrid planar-channel waveguide to achieve the two cascaded wavelength conversion process with STIRAP mechanism effects, and they realized the of two coupling coefficients in the construction of an adiabatic process in the action length [23].…”
Section: Stproducesmentioning
confidence: 99%
“…Second, we have shown that the QPM process is highly efficient so that it may be possible to use quasi-cw mode-locked lasers, and even cw lasers when combined with QPM waveguide technology to generate a comb of multiple harmonics [18]. Finally, simultaneous amplitude and phase control in a monolithic QPM crystal may also be possible [19]. Fig.…”
mentioning
confidence: 97%
“…In PRQPM, binary functions are multiplied to produce a desired modulation, which has multiple Fourier components. [25][26][27][28] The modulation function of the nonlinear coefficient is obtained via Fourier analysis of the multiplied binary function. Because the nonlinear coefficients are proportional to the coupling coefficients, the duty-cycle parameter in the function determines the magnitude of the coupling coefficients for each process.…”
mentioning
confidence: 99%